Breast cancer screening at IIUM breast centre : 7 year review of college of radiology mammogram subsidy programme(2004-2010) - Che Mohamed, Siti Kamariah; Hassan, Radhiana; Abdul Rashid, Mohd Amran; Yahaya, Azura Sharena; Mohamad Nordin, Ellyda; Zaini, Izwan Zanni; Abdul Samad Cheung, Humairah (2011)
Mammography offers the best chance of detecting early breast cancer. Subsidised mammography programmes are available in our country in the absence of national level population screening. The IIUM Breast Centre is an accredited mammogram provider under the College of Radiology Subsidised Mammography Programme (CMP) from 2004. Screening for breast cancer was done at the Centre under this special programme for 2539 selected Malaysian women during this 7 year period. The results of the screening and cancer detection rate were presented.